Analisis Reaksi Investor di Bursa Efek Indonesia pada Pelantikan Joko Widodo - Karina, Komang Lia; Sujana, I Nyoman; Irwansyah, M. Rudi (Universitas Pendidikan Ganesha, 2020)
This study aimed to analyze the reaction of investors on Indonesia Stock Exchange to the inauguration of the 8th President by observing whether there were any significant differences in abnormal returns and stock trading volume activities before and after the event. The observation period used in this study was 10 days, with details of each 5 days before and after the President's inauguration event that occurred on 20 October 2019. This research was quantitative research and used daily transaction data on the market capital as a secondary data source. The samples used were companies that were included in the LQ45 stock index for the period August 2019 - January 2020. A non-parametric test in the form of Wilcoxon test was used to test the hypothesis. The results of this study showed that there were no significant difference in abnormal return and stock trading volume activity in the period before and after the event. This was evidenced by the probability value above the significance level of 5%. Thus, the results of this study were stated that there was no reaction from the investor related to the event of the inauguration of the 8th President in Indonesia.